The Determinants of Foreign Direct Investment: A Vecm Approach - Silky Vigg Kushwah; Manan Garg (International Journal of Accounting & Business Finance, 2020)
The paper investigates the nexus between foreign direct investment (FDI) and macroeconomic variables namely trade openness, oil prices, stock index returns, GDP, exchange rate in India. FDI is considered as the dependent variable whereas macroeconomic variables are considered as independent variables. Using the Vector error correction model (VECM), we examine both the short-run and long-run relationship between FDI and macroeconomic variables over the period 2007-2019. Based on the existing literature, interest rate and inflation are considered as the controlled variables in the study. Co-integration is found in the time series variables using the Johansen Co-integration test and hence, restricted VAR (VECM) is applied to examine the nexus. Empirical evidence indicates that neither there is long term nor short term relationship between FDI inflows and underlying macroeconomic variables of the study. Although, the results highlight that FDI is significantly and positively influenced by its own lags. Therefore within the specified scope, the study suggests that liberal and flexible government policies on foreign investment may not only mark a surge in FDI inflows but will also encourage further investments by foreign individuals and companies in India.
Keywords: Foreign direct investment (FDI); Macroeconomic variables; Co-integration; vector error correction model (VECM)